Zulifah Chikmawati PENGARUH MODEL KEPEMIMPINAN TERHADAP KINERJA KARYAWAN DI LEMBAGA BIMBINGAN BELAJAR SSC (SONY SUGEMA COLLEGE) BUDURAN SIDOARJO : Program Studi Manajemen, Universitas Nahdlatul Ulama Sidoarjo *e-mail: zulifahhikmaawati@yahoo.com - Zulifah Chikmawati (GREENOMIKA, 2019)
This research was conducted at the study institute of Sony Sugema College (SSC), Buduran Sidoarjo. The research has a purpose to find out how much influence the Leadership Style has on Employee Performance at Sony Sugema College (SSC), Buduran Sidoarjo. This research uses quantitative research methods and data processing is done by SPSS software. In this case, Employee Performance is the dependent variable, while the Leadership Style is an independent variable. This study uses regression analysis with 30 respondents. The results of data processing obtained beta values of Leadership Style of 0.101 with a sig value. amounting to 0.003 or 0.3%. Sig value 0.003 <0.05 indicates that the Leadership Style has a significant effect on the performance of employees at the Sony Sugema College (SSC) tutoring institution, Buduran Sidoarjo.